THE ROLE OF LEGAL OFFICE IN HANDLING CASES OF SEXUAL HARASSMENT TOWARD IMPOVERISHED SOCIETY - Rasikhah, Nailah; Hariyanto, Sugeng (Universitas Tanjungpura, 2023)
Sexual harassment is something that is common in Indonesia and other countries because the cases occur almost every year. Legal protection for victims of sexual harassment is stated in the Law. But in fact, Indonesian law itself has not been able to fully provide firm legal consequences for perpetrators of harassment and protection for victims. In fact, there is still legal inequality between victims and perpetrators due to social inequality where the victim comes from an impoverished society so the perpetrator can pass the trial because they can afford to pay a lawyer to defend himself. Therefore the purpose of this study is to find out how is the role of law enforcement officials toward the victims of sexual harassment, especially women. This study used the descriptive qualitative method. The data was obtained from Indonesian language-based books. This study used the theory of Karl Marx which states that there is a conflict between social classes, where the interests are conflicting and irreconcilable because of different social and economic order positions. From the research, it can be concluded that legal injustice that occurs in Indonesia is due to law enforcement officials who are not wise or cannot take a good role in handling cases of sexual harassment against women. In addition, it is influenced by social class where it is difficult for lower-class people to get justice because upper-class people dominate the law which will lead to divisions in the communities.